'It isn't over until the fuel cell sings': A reassessment of the US and French pledges of nuclear assistance in the 1970s. Issue 1 (23rd February 2018) - Rabinowitz, Or; Sarkar, Jayita
ABSTRACT: Based on newly declassified archival documents, the aim of this study is to contribute to an improved understanding of the evolution of the non-proliferation regime through an examination of US and French nuclear cooperation agreements in the latter half of the 1970s. The four pledges of nuclear assistance examined – US assistance to Egypt and Israel, and French assistance to Pakistan and South Korea – failed to materialise by the end of the decade. Why did that happen? What caused the four pledges to fail? We find that the 1974 Indian nuclear explosion and the emergence of opposing domestic factions on the nuclear front in the supplier states generated major changes in US and French nuclear export policies, and also contributed to the development of a collaborative partnership between the two competing nuclear exporters, on the other.